2014
DOI: 10.1002/gps.4099
|View full text |Cite
|
Sign up to set email alerts
|

The impact of reminiscence on the quality of life of residents with dementia in long‐stay care

Abstract: Reminiscence may, in certain circumstances, be an effective care option for people with dementia in long-stay settings with potential to impact positively on the quality of life of residents.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
75
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 44 publications
(81 citation statements)
references
References 25 publications
5
75
1
Order By: Relevance
“…This result was consistent with the results of the previous studies . O'shea et al reported that reminiscence had a positive effect on quality of life, as measured in the short‐term over an 18‐ to 22‐week period, significantly when examined on a per‐protocol basis . Life satisfaction can be viewed as a cognitive aspect of perceived quality of life .…”
Section: Discussionsupporting
confidence: 91%
“…This result was consistent with the results of the previous studies . O'shea et al reported that reminiscence had a positive effect on quality of life, as measured in the short‐term over an 18‐ to 22‐week period, significantly when examined on a per‐protocol basis . Life satisfaction can be viewed as a cognitive aspect of perceived quality of life .…”
Section: Discussionsupporting
confidence: 91%
“…Post intervention, the “physical component summary score” showed an improvement, and this score was higher than the national average value for 70–79 year-old individuals. Previous studies have reported that listening, singing, and RT improve QOL of individuals with dementia2, 9 ) . As our intervention included these three factors, we could provide relative improvement in QOL in short sessions.…”
Section: Discussionmentioning
confidence: 95%
“…Reminiscence therapy (RT) also affects cognitive function, BPSD, and QOL in elderly individuals with and without dementia6,7,8,9 ) . In RT, people speak about their experiences or memories in a group using pictures as clues.…”
Section: Introductionmentioning
confidence: 99%
“…The strategies used to maximise the inclusion of people with dementia in this study no matter their stage of dementia are described elsewhere (O'Shea et al . ). Relatives had an immediate member of their family (mother or father) living in the long‐term care facility.…”
Section: Methodsmentioning
confidence: 97%
“…The person with dementia's assent to be involved was obtained at all stages (O'Shea et al . ) irrespective of whether consent had been given directly or by proxy. Researchers continuously assessed the person's assent during data collection.…”
Section: Methodsmentioning
confidence: 99%